2010
DOI: 10.1055/s-0030-1254296
|View full text |Cite
|
Sign up to set email alerts
|

Rectovaginal Fistulas

Abstract: Rectovaginal fistulas are abnormal epithelial-lined connections between the rectum and vagina. They can be quite bothersome to both the patient and the surgeon due to their irritating and embarrassing symptoms and high failure rate after repair. An individualized, systematic approach to these fistulas based on their size, location, and etiology provides a more concise treatment plan. Treatment options of medical therapy, advancement flaps, plugs, fistula ligation, and tissue interposition are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
66
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 75 publications
(75 citation statements)
references
References 20 publications
0
66
0
1
Order By: Relevance
“…It is also important to classify RVF into simple and complex due to the different treatment algorithms. 2 Simple fistulas are defined as low lying fistulas, less than 2.5 cm in size, and associated with simple trauma or infection. Complex RVFs are defined as size greater than 2.5 cm, high fistulas near the cervix, associated with inflammatory bowel disease, or are recurrent.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It is also important to classify RVF into simple and complex due to the different treatment algorithms. 2 Simple fistulas are defined as low lying fistulas, less than 2.5 cm in size, and associated with simple trauma or infection. Complex RVFs are defined as size greater than 2.5 cm, high fistulas near the cervix, associated with inflammatory bowel disease, or are recurrent.…”
Section: Discussionmentioning
confidence: 99%
“…Complex RVFs are defined as size greater than 2.5 cm, high fistulas near the cervix, associated with inflammatory bowel disease, or are recurrent. 2 Simple RVFs can be repaired using the endo-rectal advancement flap, however, complex RVFs involve larger surgeries. In high RVFs the transabdominal approach is often sited with the repair involving interposition of healthy tissue between the rectum and vagina with surgical modalities including low anterior resections, abdominal perineal resections, and complex muscle flaps.…”
Section: Discussionmentioning
confidence: 99%
“…Various causes of lower third RVFs have been reported: abscess of the rectovaginal septum, lymphogranuloma venerum, tuberculosis, abscess of bartholin's gland and HIVassociated bacterial and viral infections. 10,11 In developed countries, the main cause of non-obstetrical RVF is Crohn's disease that is less frequent in tropical regions.…”
Section: Aetiologymentioning
confidence: 99%
“…Kouadio et al reported 37 cases of RVFs of which 11 were of infectious origin. 10,11 Bankole et al described 6 cases of pediatric infectious RVFs of which 5 were in HIV patients. 2 Lymphogranuloma venereum, genital tuberculosis and perineal abscess have been identified by some authors as causes of RVF.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation